RELATIONSHIP BETWEEN BLOOD GLUCOSE LEVEL DURING ADMISSION AND CLINICAL OUTCOME OF STROKE PATIENT IN THE STROKE UNIT OF RSUP DR. SARDJITO - , SITI NAZIRA BINTI HJ ABD AZIZ ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is the leading neurologist diseases with the highest number of death and physical impairment. Hyperglycemia appears to be associated with more severe stroke, as assessed either with a clinical stroke scale or by brain lesion volume measurement. The availability of this data is hoped to be helpful in national stroke combating programs in Indonesia. This study will benefit many people to understand more about stroke itself and preventing more severe outcome of stroke patient. determine whether there is strong relationship between blood glucose level and the Objective of the study: To physical function of stroke patient. Methods: This is an observational study using the retrospective method. All the data from this study will be obtained from the medical record of the acute ischemic stroke patients who have admitted to stroke unit of RSUP DR. Sardjito in the year 2012. 45 patients fulfilled the inclusion and exclusion criteria. The characteristics of the data were described in mean and standard deviations. Then the correlation coefficient is further tested with Sperman correlation using SPSS. Result: There is with weak correlation between blood glucose level and GMSS score. The correlation revealed that insignificant correlation between them. (r= 0.140